Implementasi Metode SAW dan TOPSIS dalam Penentuan Kinerja Karyawan Terbaik pada Perusahaan Penukaran Uang - Nia Nuraeni (Jurnal Informatika Universitas Pamulang, 2020)
Employees are the most important part in a company. In the process of managing employees or human resources department (HRD), it can affect many aspects that determine the success of the work at the company. In the process, the employee performance appraisal at money exchange companies is done manually, so that the employee performance appraisal is less objective and requires a long assessment process so it is inefficient and ineffective. With the system used in the performance appraisal process, it is hoped that it can help companies to assess employee performance quickly and precisely and objectively determine the best performing employees. The methods used in this employee performance appraisal system are the SAW and TOPSIS methods, where the results of the best employee performance appraisal process in both methods produce the same employee data recommendations.